Pesantren Dalam Perubahan Sosial di Indonesia - Siti Mas'ulah (At-Ta'lim : Media Informasi Pendidikan Islam, 2019)
Abstract: Pesantren in Social Changing in Indonesia. At this time, Islamic boarding school (pesantren) have become part of the national education system which has its own peculiarities which have a major role in education and teaching since before the Independence of the Republic of Indonesia until now. Based on the social theory of social change by Peter L. Berger and Thomas Luckmann, Islamic boarding school (pesantren) experienced dynamics typology as follows, namely salafiyah Islamic boarding school (pesantren) teaches pure Islamic knowledge without the addition of general sciences, its management system is centered on kiai (Grand-Teacher) figures. Second, the Khalaf Islamic boarding school (pesantren) tries to combine the system of classical and modern teaching, so that the management developed is modern management and does not rely solely on kiai (Grand-Teacher) figures. Third, the comprehensive kiai (Grand-Teacher) figures combine modern and classical teaching systems with a faster and more dynamic power of change than the khalaf Islamic boarding school.Abstrak: Pesantren Dalam Perubahan Sosial Di Indonesia. Pada saat ini, pesantren telah menjadi bagian dari sistem pendidikan nasional yang memiliki kekhasan tersendiri yang memiliki peran besar dalam pendidikan dan pengajaran sejak sebelum Kemerdekaan Republik Indonesia hingga kini.   Berdasarkan teori sosial perubahan sosial Peter L. Berger dan Thomas Luckmann, pesantren mengalami dinamika tipologi sebagaimana berikut, yakni pesantren salafiyah mengajarkan ilmu-ilmu Islam murni tanpa ada penambahan ilmu-ilmu umum, sistem manajemennya berpusat pada figur kiai. Kedua, pesantren khalaf berusaha mengabungkan sistem pengajaran klasikal dan modern, sehingga manajemen yang dikembangkan adalah manajemen modern dan tidak bertumpu semata-mata pada figur kiai. Ketiga, pesantren konprehensif menggabungkan sistem pengajaran modern dan klasikal dengan daya perubahan yang lebih cepat dan lebih dinamis daripada pesantren khalaf.